Explaining Ourselves: Human-Aware Constraint Reasoning - Freuder, Eugene (Proceedings of the AAAI Conference on Artificial Intelligence, 2017)
Human-aware AI is increasingly important as AI becomes more powerful and ubiquitous. A good foundation for human-awareness should enable ourselves and our "AIs" to "explain ourselves" naturally to each other. Constraint reasoning offers particular opportunities and challenges in this regard. This paper takes note of the history of work in this area and encourages increased attention, laying out a rough research agenda.